PENERAPAN MODEL PENGAJARAN LANGSUNG (DIRECT INSTRUCTION) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SEKOLAH DASAR - N, Lazim (Jurnal Pendidikan Guru, 2017)
This research is based on the low learning outcomes of science students of grade IV of SD Negeri 030 Tampan Pekanbaru, caused by the lesson learned strategy applied by teachers is less precise. The action taken is the Implementation of the Direct Teaching Model. This study aims to improve science learning outcomes of fourth graders in SD Negeri 030 Tampan Pekanbaru through Implementation of Direct Teaching Model. This research was conducted in September 2011. The subjects of the study were the fourth grade students of SD Negeri 030 Tampan Pekanbaru which amounted to 25 people. This study presents students learning outcomes used to measure student learning outcomes seen from daily repetition I in cycle I and daily repetition II in cycle II, the average of students in the final exam of the first cycle increased by 9.4 points from a base score of 59.2 to 68.6 while in cycle II increased by 11.4 points from cycle I to 80. For teacher activity first meeting cycle I percentage equal to 66,25% and second meeting cycle I percentage equal to 72,5%, first meeting second cycle percentage equal to 77,5% and second meeting in cycle II percentage equal to 86,25%. While on student activity at first meeting of cycle I was 60,75%, second meeting of cycle I was 80,25%, first cycle second meeting was 90,87%, and second meeting second cycle percentage was 95,37%. From the results of the above study note that the Implementation of Direct Instruction Model (Direct Instruction) can improve science learning outcomes of fourth grade students of Primary School.